Effect of trifluoromethyl substituents on birefringence of polystyrene. (12th May 2016) - Tagaya, Akihiro; Koike, Kotaro; Koike, Yasuhiro; Okamoto, Yoshiyuki
Abstract : Transparent thermoplastic polymers that exhibit no birefringence are ideal for optical components such as optical films for liquid crystal displays and various lenses. Copolymerization of a positive birefringent monomer with a negative monomer is an effective technique for obtaining low birefringent polymers, especially zero‐photoelastic birefringence polymers that exhibit no photoelastic birefringence even during elastic deformation. We prepared four types of trifluoromethyl‐substituted polystyrenes. By substituting hydrogens at the ortho or meta positions of the benzene ring of polystyrene, we demonstrated that poly(2‐(trifluoromethyl)styrene), poly(3‐(trifluoromethyl)styrene), and poly(3, 5‐bis(trifluoromethyl)styrene) had negative photoelastic coefficients. However, poly(4‐(trifluoromethyl)styrene) had a positive photoelastic coefficient similar to that of polystyrene. Based on these results, we synthesized a zero‐photoelastic birefringence polymer of poly(2‐(trifluoromethyl)styrene‐co‐4‐(trifluoromethyl)styrene) (55/45 wt.) exhibiting no photoelastic birefringence in elastic deformation, in which the positive photoelastic birefringence of the poly(4‐(trifluoromethyl)styrene) unit was compensated for by the negative photoelastic birefringence of the poly(2‐(trifluoromethyl)styrene) unit. The discovery of polymers having negative photoelastic coefficients is valuable for the design and synthesis of zero‐photoelastic birefringence polymers. The four types of trifluoromethyl‐substituted polystyrenes are promising optical materials because they have high transparency (transmittance > 89–92% for 27–34‐µm thickness films) in the visible and near‐infrared regions and a high decomposition temperature of approximately 400°C. Copyright © 2016 John Wiley & Sons, Ltd.